Circadian profiles of progesterone, gonadotropins, cortisol and corticotropin in cycling and postmenopausal women. (2nd January 2018) - Caufriez, Anne; Leproult, Rachel; Copinschi, Georges
ABSTRACT: Little is known about the regulation of temporal variations of progesterone over the 24-hr span in young cycling women as well as in postmenopausal women. The purpose of the present study was to investigate the relationships between diurnal variations of progesterone and diurnal variations of hormones of the gonadotropic and corticotropic axes, and to provide further information on the source of progesterone secretion under physiological conditions. Twenty-four-hour hormonal profiles were explored under well-controlled laboratory conditions in 10 healthy women (21–36 yr old) with normal ovulatory cycles during early-mid follicular and late luteal phases, and in 8 healthy postmenopausal women (48–74 yr old). In young cycling women, significant positive relationships were found between progesterone and follicle-stimulating hormone (FSH) – but not luteinizing hormone (LH) – profiles during late luteal phase. Conversely, during follicular phase, significant positive relationships were evidenced between progesterone and cortisol profiles, but not between progesterone and FSH or LH. In postmenopausal women, strong positive correlations were found between progesterone and corticotropin (ACTH) or cortisol profiles. The present results indicate that during late luteal phase, temporal progesterone profiles are associated with FSH rather than with LH profiles. They also provide evidence that adrenal cortex is a major – or possibly the only – source of progesterone production during the follicular phase of the normal ovulatory cycle, and probably the only source after menopause.